Business Model Innovation in Small Ventures: A Resource-Based Perspective on Managerial Ties and External Ecosystems - Grace Yulianti; Mohammad Chaidir (STIE KASIH BANGSA, 2025)
This qualitative literature review investigates the role of managerial ties, external ecosystems, and the resource-based perspective in fostering business model innovation (BMI) in small ventures. By examining a range of studies, the review highlights how small businesses leverage managerial ties to access critical resources, knowledge, and networks that enable innovation. Additionally, the review explores the importance of engaging with external ecosystems, such as suppliers, customers, and research institutions, in enhancing the business model innovation process. Drawing on the resource-based view (RBV), the study emphasizes the significance of both tangible and intangible resources for successful innovation. The findings suggest that small ventures with strong managerial ties and dynamic capabilities are more likely to navigate the complexities of BMI. This review contributes to a deeper understanding of the factors that influence business model innovation in small ventures, offering valuable insights for both researchers and practitioners.